# How do you differentiate #y=1/(x+ke^s)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate the function ( y = \frac{1}{x + ke^s} ) with respect to ( x ), you can use the chain rule. The derivative is:

[ \frac{dy}{dx} = -\frac{1}{(x + ke^s)^2} ]

The chain rule states that if ( y = f(g(x)) ), then ( \frac{dy}{dx} = f'(g(x)) \cdot g'(x) ). In this case, ( f(u) = \frac{1}{u} ) and ( g(x) = x + ke^s ). Thus, ( f'(u) = -\frac{1}{u^2} ) and ( g'(x) = 1 ). Therefore, ( \frac{dy}{dx} = -\frac{1}{(x + ke^s)^2} ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you differentiate #f(x)=5x^4-3x^2+2#?
- What is the slope of the tangent line of #sqrt(y-e^(x-y))= C #, where C is an arbitrary constant, at #(-2,1)#?
- How do you implicitly differentiate #-1=sinxy #?
- What is the derivative of #2x(4-x^2)^(1/2)#?
- How do you integrate #f(x)=3^(5x-1)/e^(4x)# using the quotient rule?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7